Non-invasive and quantitive analysis of flatfoot based on ultrasound - Jiang, Zhende; Zhang, Qianpeng; Ren, Lei; Qian, Zhihui (Frontiers in Bioengineering and Biotechnology, 2022)
Flatfoot is a common foot deformity that seriously affects the quality of life. The aim of this study is to develop an accurate and noninvasive method for the diagnosis of flatfoot based on B-mode ultrasound. In this study, 51 patients (the flatfoot group) and 43 healthy subjects (the control group) were included. The plantar fascia angle, a new measurement for use in the diagnosis of flatfoot is proposed, as determined using B-mode ultrasound. For comparison, the calcaneal pitch angle and medial cuneiform height were also measured using lateral X-radiography, based on traditional diagnostic methods. The intraclass correlation values of the plantar fascia angle, the calcaneal pitch angle, and the medial cuneiform height were all more than 0.95, and there is a moderate correlation (r = 0.51) between the medial cuneiform height and the calcaneal pitch angle, and an excellent correlation (r = 0.85) between the plantar fascia angle and the calcaneal pitch angle. The optimal cutoff value, sensitivity, and specificity for medial cuneiform height in flatfoot diagnosis were 12.8 mm, 93.0%, and 54.9%, respectively. The optimal cutoff value, sensitivity, and specificity for plantar fascia angle in flatfoot diagnosis were 9.8°, 97.7%, and 94.1%, respectively. The proposed plantar fascia angle has good sensitivity and specificity in diagnosing flatfoot, therefore supplying a new approach for the noninvasive diagnosis of flatfoot.